Effects of Boswellia Serrata and Whey Protein Powders on Physicochemical Properties of Pork Patties - Fengqi Yang; Won-Young Cho; Nayeon Lee; Da-Hee Kim; Jihye Lee; Hyun-Jin Lee; Han Geuk Seo; Chi-Ho Lee (Foods, 2020)
Processed meat products are prone to oxidative damage and quality decline during storage; however, these problems can be mitigated by the proper formulation of meat productions. This study evaluated the effects of natural anti-oxidants found in Boswellia serrata (B), whey protein powder (W), and their combination on pork patties during storage, exploring changes in textural properties and lipid oxidation susceptibility. The 2% whey-added group exhibited a higher crude protein content than the untreated control group. The highest water-holding capacity and lowest cooking losses were observed in mixed-additive groups (WB1 (2% W/0.5% B) and WB2 (2% W/1.0% B), and the highest sensory scores for overall acceptability were obtained for WB1. Adding B. serrata can neutralize the hardness caused by whey powder, thereby improving palatability. From 7 d (days 7), the extents of lipid oxidation, determined using 2-thiobarbituric acid-reactive substances (TBARS) analysis, for the WB1 and WB2 groups were significantly lower than that of the control group. The WB1 and WB2 groups exhibited substantially suppressed total bacterial colony and Escherichia coli counts relative to the control group. Our findings suggest that the additive combination of B. serrata and whey protein powders can suppress lipid oxidation, improve storage stability, and enhance textural properties in the production of functional pork patties.